The determinants demand of the residential property: case study in Kajang / Muhammad Hafizi Mohd Rafie - Mohd Rafie, Muhammad Hafizi (Faculty of Business Management, University Teknology MARA, 2018)
The aim of this study is to determine the key factors that the purchasers consider before making decision to purchase the residential property. The study uses primary data, which means that the data and information will be gained from the respondents. The factors involve in this study are location, neighborhood, structure attributes and financial. The factors are taken based on previous study by previous researchers. The data will be collected from the respondents through questionnaire distributed to them. The questionnaire will be distribute to those who have purchased the residential property in Kajang. 100 questionnaire forms will be answered by the respondents who qualified the criteria in this study. The data will then only be collected from community in Kajang. The data and information collected will be used to generate the analysis. Descriptive analysis, factor analysis, analysis of variance, reliability test and regression will be used to trigger the results of this study. The results showed that structural attributes factor do affect the demand of the residential property. The results revealed will help the future researchers and potential readers to gain better understanding on the residential property. By understanding the key factors behind purchasing residential property, purchasers of the property would be able to gauge the factors that matter most before purchasing the property.